1998
DOI: 10.1103/physrevb.57.2904
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-dependent electrical resistivity ofRCo2compounds(R= rare earth)

Abstract: Studies of the electrical resistivity were carried out under applied hydrostatic pressures up to 20 kbar and in the temperature range from 1.5 K to room temperature. The pressure dependence of the magnetic-ordering temperatures and the suppression of spin fluctuations in the paramagnetic temperature regime have been deduced from the variation of characteristic features in (T, P). Grüneisen parameters of the magnetic-ordering temperature T C and the spin-fluctuation temperature T SF have been obtained and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 53 publications
9
40
0
6
Order By: Relevance
“…Therefore, it is quite possible that the reduction in MCE caused by the weakening of IEM is just compensated by the increase in MCE arising out of the reduction in T C . Therefore, the insensitiveness of MCE on pressure seen in the case of ErCo 2 is consistent with the observations made by Hauser et al [55]. Fig.…”
Section: Effect Of Pressure On the Magnetocaloric Effectsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, it is quite possible that the reduction in MCE caused by the weakening of IEM is just compensated by the increase in MCE arising out of the reduction in T C . Therefore, the insensitiveness of MCE on pressure seen in the case of ErCo 2 is consistent with the observations made by Hauser et al [55]. Fig.…”
Section: Effect Of Pressure On the Magnetocaloric Effectsupporting
confidence: 81%
“…The insensitiveness of MCE on applied pressure in the case of ErCo 2 is due to the fact that the strength of IEM has diminished only nominally even at a pressure of about 7.7 kbar. Hauser et al [55] have indeed reported that the discontinuity (at T C ) in the magnetic contribution to the electrical resistivity in ErCo 2 decreases to about 60 % as the pressure is increased from 1 bar to ~16 kbar, which is attributed to the reduction in the strength of IEM. In view of this, it is reasonable to assume that for a pressure of 7.7 kbar, the reduction in the IEM strength is not very much and therefore would contribute only to a nominal reduction in max M S ∆ .…”
Section: Effect Of Pressure On the Magnetocaloric Effectmentioning
confidence: 99%
“…For this purpose, H cr is defined as the peak field in the plots of d(MR)/dH and dM/dH versus H. Clearly, the variation of H cr in the solid solution is consistent with the trend seen in the external pressure experiments, compelling us to conclude that H cr decreases with decreasing volume. The positive volume coefficient of H cr interestingly follows the behavior seen in inverse metamagnetic itinerant systems [8,9]. This naturally raises a question whether magnetic fluctuations as in 'inverse metamagnetism' can be invoked for the observed jump in positive MR. We make the following speculative points in support of this, though additional studies (for instance, neutron diffraction) are warranted to clarify further.…”
Section: IVmentioning
confidence: 81%
“…In particular, the above mentioned MR anomaly was in fact observed in the cubic Laves phase family, RCo 2 . These binary compounds have been subjected to intense experimental investigations over a period of two decades [5][6][7][8][9]. In these systems, the existence of field-induced transitions and MR anomalies is known to originate from the existence of a peak in the Co 3d density of states in the vicinity of Fermi level.…”
Section: Imentioning
confidence: 99%
“…NdCo 2 and PrCo 2 do not present the abrupt drop in resistivity shown in the Er, Ho, and Dy Laves Co phases, as clearly shown by several studies: see, for example, the recent reviews by Duc and Brommer 11 and Gratz and Markosyan, 12 but above all those by Hauser et al, 13 Deenadas et al, 9 and Duc et al, 4 which in our opinion can only be interpreted as a clear evidence of a SOT in PrCo 2 and NdCo 2 at the Curie temperature. Indeed the authors of the cited works do identify PrCo 2 and NdCo 2 magnetic orderings as SOTs in all those cases, contrary to the reinterpretation of Forker et al of their works.…”
Section: Previous Resultsmentioning
confidence: 73%